Aristotle and Medieval Philosophy. The Genre of Comments - Florido, Francisco León (Scripta Mediaevalia, 2022)
In the High Middle Ages, the influence of Aristotle was already considerable, but it was practically limited to commentaries on Categories. On the other hand, Metaphysics was known in Christian Europe late, and it is only at the beginning of the XIII century when it will be completely accessible to the Latin world. The reception of Aristotle by the Latins takes place through translations, commentaries, paraphrases, short writings on different topics and contributions in encyclopedic treatises. Generally, medieval commentaries on Aristotle, and especially on Metaphysics, are divided into two groups: literal expositions and commentaries per modum quaestionis. Both methods were employed in the century from 1250 to 1350, when Metaphysics became the center of controversy among European theologians.